PENGARUH MODEL PEMBELAJARAN GAME-BASE LEARNING DENGAN MEDIA POKEMON TCG UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG ARITMATIKA DASAR DI SD - Anggi, Muhamad; Puspitasari, Wina Dwi; Cahyaningsih, Ujiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the importance of innovative learning media that can help elementary school students understand basic arithmetic operations. The Pokemon Trading Card Game (TCG) was chosen as a game-based medium that is expected to make learning mathematics more enjoyable. The purpose of this study was to determine the effect of using Pokemon TCG on students' arithmetic skills and to compare the learning outcomes between classes that used this medium and conventional classes. The research used a quasi-experimental method with a pretest–posttest control group design. The research subjects were second-grade students at SDN Karamat 1 (23 students) as the control class and SDN Tenjolayar 3 (27 students) as the experimental class. The instrument used was a valid and reliable 10-question descriptive test on basic arithmetic operations. Data analysis included descriptive tests, Wilcoxon, Mann-Whitney, and N-Gain calculations. The results showed a significant increase in the experimental class after using Pokemon TCG (p < 0.05). Although there was no significant difference in the posttest results between classes (p > 0.05), the N-Gain values of both classes were high, with the experimental class slightly superior.